Class, Gender, and Rhoticity: The Social Stratification of Non-Prevocalic /r/ in Edinburgh Speech. (September 2017) - Dickson, Victoria; Hall-Lew, Lauren
Despite the prominence of socioeconomic status as a factor in models of English variation, few studies have explicitly considered speakers whose social class status changed over their lifetime. This paper presents an auditory and acoustic analysis of variation in non-prevocalic /r/ among middle-aged adults from Edinburgh, Scotland. The speakers represent three groups: the Established Middle Class (EMC) and the Working Class (WC), both of which are characterized as socioeconomically non-mobile, and a third group we call the New Middle Class (NMC), comprising individuals born to working-class families and living middle-class lives at the time of data collection. The results demonstrate that realizations of /r/ have a significant correlation with socioeconomic status, and that the effect of class further interacts with gender. NMC speakers demonstrate the highest level of rhoticity of all three groups. In contrast, WC men show extensive derhoticization and deletion, while WC women show patterns of rhoticity that are more comparable to the NMC women. The EMC speakers show more non-rhoticity than either the NMC speakers or the WC women. A consideration of the indexical value of weak rhoticity highlights the need for more robust phonetic measures distinguishing non-rhoticity from derhoticization, and to that end we consider the cue of post-vocalic frication. Overall, the results point to the need to conceptualize socioeconomic status as potentially fluid and changeable across the lifespan, thereby improving models of the relationship between social class and linguistic variation.